2018
DOI: 10.1002/bmc.4212
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics study of ginkgolide A, B and the effect of food on bioavailability after oral administration of ginkgolide extracts in beagle dogs

Abstract: Ginkgolides are the primarily active components in Ginkgo products that are popular worldwide. However, few studies have evaluated the bioavailability of ginkgolides and the effects of food on it after oral administration of ginkgolides. In this article, pharmacokinetics and absolute bioavailability of the primary components in ginkgolide extracts were evaluated in beagle dogs. For the first time, we showed that the fed dogs had significantly increased area under the concentration-time curve and peak concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In this context, there are several aspects of this observation that need to be addressed. First, a study of the pharmacokinetics and bioavailability of GA and ginkgolide B using beagle dogs has revealed that the free form of these prototype ginkgolides and their absolute bioavailabilities are high . This suggests that administration of ginkgolides is able to promotes the in vivo exposure to and in vivo bioavailability of GA. Second, there is evidence to support the idea that GA might find it difficult to pass through the blood–brain barrier. , Thus, this becomes one possible reason why GA is not able to boost the memory behavior of J20 mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there are several aspects of this observation that need to be addressed. First, a study of the pharmacokinetics and bioavailability of GA and ginkgolide B using beagle dogs has revealed that the free form of these prototype ginkgolides and their absolute bioavailabilities are high . This suggests that administration of ginkgolides is able to promotes the in vivo exposure to and in vivo bioavailability of GA. Second, there is evidence to support the idea that GA might find it difficult to pass through the blood–brain barrier. , Thus, this becomes one possible reason why GA is not able to boost the memory behavior of J20 mice.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Beagle dogs receiving, by oral administration, ginkgolide extracts (6.0 mg/kg) containing 28% (w/w) ginkgolide A and 63% (w/w) ginkgolide B showed that the bioavailability of the ginkgolides A and B increased significantly when the extracts were given together with food (Aa et al., 2018 ). The absorption rate for ginkgolide A and ginkgolide B increased from 34.8% and 5.2% in fasted dogs to 78.6% and 17.0% in dogs receiving the compounds together with a meal.…”
Section: Assessmentmentioning
confidence: 99%
“…Ginkgo biloba leaf contains many components, but most of the bioactivity is attributed to the terpene lactones and flavonols. Many constituents are largely unabsorbed in parent forms, such as the terpene lactones [ 128 , 129 , 130 ], flavonols, and glycosides, some of which must be broken down into readily absorbable compounds. This is where the gut microbiota may play a significant role, providing enzymes such as glycosidase and metabolism to break down the glycosides and release the absorbable forms and aglycones [ 131 , 132 , 133 ].…”
Section: Bioavailability Bioactivity Of Gle Components and Antibiotic...mentioning
confidence: 99%